A Phase 3 clinical trial validating the potency and safety of an innovative, extra‐long‐acting interferon in chronic hepatitis C. Issue 11 (10th October 2022) - Chen, Chi‐Yi; Chuang, Wan‐Long; Qin, Albert; Zhang, Wen‐Hua; Zhu, Li‐Ying; Zhang, Guo‐Qiang; Chen, Jyh‐Jou; Lo, Ching‐Chu; Zhou, Xinmin; Mao, Xiaorong; Shang, Jia; Kuo, Hsing‐Tao; et al.
Abstract: Background and Aim: Ropeginterferon alfa‐2b is a novel mono‐pegylated, extra‐long‐acting interferon. It is administered infrequently and showed good tolerability and clinical activity for the chronic hepatitis B or C treatment in our previous Phase 2 clinical trials. This study aims to validate the potency and safety of this novel agent in a Phase 3 chronic viral hepatitis setting. Methods: Patients with chronic hepatitis C genotype 2 were randomized to receive subcutaneous injections of ropeginterferon alfa‐2b biweekly or the conventional pegylated interferon alfa‐2b weekly for 24 weeks, combined with ribavirin. The primary endpoint was to assess the safety and antiviral potency of ropeginterferon alfa‐2b by the non‐inferiority in sustained virologic response at 12 weeks after treatment. Results: A total of 222 patients were enrolled. Ropeginterferon alfa‐2b group showed a favorable safety profile. Side effects that were generally associated with prior interferon therapies, including neutropenia, asthenia, fatigue, alopecia, dizziness, decreased appetite, nausea, flu‐like symptoms including myalgia, pyrexia, and headache, and administration site reactions, were notably less in the ropeginterferon alfa‐2b group. The cumulative incidence of adverse events of special interest was also notably higher in the control group. The primary endpoint was met and ropeginterferon alfa‐2b showed a better SVR12 rate of 79.8% than 71.9% of the control group. Conclusion: Ropeginterferon alfa‐2b is efficacious and has a favorable safety profile as compared with the conventional pegylated interferon alfa‐2b. This study together with previous Phase 2 data validated ropeginterferon alfa‐2b to be a new treatment option for chronic hepatitis C genotype 2. Abstract : The Phase 3 study demonstrated that ropeginterferon alfa‐2b is efficacious and has a favorable safety profile as compared with the conventional pegylated interferon alfa‐2b. This study together with previous Phase 2 data validated ropeginterferon alfa‐2b to be a new treatment option for chronic hepatitis C genotype 2.